Medial Patellofemoral Ligament Reconstruction - Laura E. Keeling MD; Andrew J. Curley MD; Janina Kaarre MD, MSc; Jeannette M. Joly MD; Robin V. West MD (SAGE Publishing, 2022)
Background: Recurrentlateral patellar dislocation is a devastating condition associated with different pathologies, including medial patellofemoral ligament (MPFL) injury, increased tibial tubercle to trochlear groove (TT-TG) distance, and trochlear dysplasia. This video aims to provide an overview of isolated MPFL reconstruction in a patient with recurrent patellar dislocation and chronic MPFL injury. Indications: Isolated MPFL reconstruction is indicated for patients with recurrent lateral patellar instability following an initial trial of nonoperative management, in the absence of other contributing anatomic factors. Candidates for isolated MPFL reconstruction should have a TT-TG distance of <20 mm, and normal or Dejour type A trochlear morphology. Technique Description: Semitendinosus allograft is used to reconstruct the torn or attenuated MPFL. Following diagnostic arthroscopy, an incision is made over the medial border of the patella and dissection is carried through the skin and subcutaneous tissue to the fascia. Two K-wires are over-drilled and two 3.5-mm Arthrex SwiveLock anchors are placed. The allograft is prepared and whipstitched on both sides. The central portion of the graft is tide down to the anchors. A second incision is then made on the medial side of the knee over the epicondyle. Dissection is carried down to the fascia, and palpation is used to identify Schottles' point. This is confirmed with fluoroscopy. An 8-mm drill bit is then used to drill to a depth of 60 mm on the femoral side. The grafts are passed one at a time through the femoral tunnel. The femoral side is fixed with an Arthrex BioComposite Interference Screw and the incisions are subsequently irrigated and closed in a layered fashion. Results: MPFL reconstruction demonstrates good functional and clinical outcomes with high rates of patient satisfaction and low rates of failure. A recent systematic review demonstrated an 84% rate of return to sport, improved postoperative outcomes, and pooled risks of recurrent instability and reoperation of less than 5% following isolated MPFL reconstruction. Conclusion: Isolated MPFL reconstruction should be considered for patients with recurrent patellar instability in the absence of other clinical risk factors. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.